DRINO IMBERBIS (WIEDEMANN) (DIPTERA: TACHINIDAE), A PARASITOID OF MALACOSOMA DISSTRIA HUBNER (LEPIDOPTERA: LASIOCAMPIDAE) CATERPILLARS IN IRAN (Acta Entomologica Serbica, 2017)
Malacosoma disstria Hubner (Lepidoptera: Lasiocampidae) is a widespread generalist defoliator of a wide variety of plants in Iran. This study was conducted to identify the indigenous parasitoids of the forest tent caterpillar in the Borazjan region of the Bushehr province, Iran. Samplings were conducted in different sites within a single cabbage field heavily infested with M. disstria. The forest tent caterpillars were reared in the laboratory until the emergence of parasitoids. A parasitoid species from the family Tachinidae was found, reared, and identified as Drino imberbis (Wiedemann). Malacosoma disstria is a new host record for D. imberbis in Iran.